A Case Study Of Haw Par Healthcare Limited - Lim, Mei Theng (2005)
The main objective is to relook Haw Par Healthcare Limited at the business from a more strategic perspective, exploit its core competencies, and gain a competitive advantage to achieve an above average returns.